(untitled) (International Seven Journal of Health Research, 2023)
This study aims to analyze the scientific evidence on the effects of COVID-19 on patients with pulmonary tuberculosis. This is an integrative review, in which the Google Scholar, Scielo, Virtual Health Library (VHL) and PubMed databases were used to select the articles, which were carried out between April 26 and May 20, 2021. The descriptors used were: "tuberculosis", "coronavirus infection", "Mycobacterium tuberculosis" combined with the Boolean operator "AND and OR". The results obtained in the literature analyzed pointed to some important issues, as it was observed that patients with MTB contaminated by SARS-CoV-2, have an accelerated symptomatic evolution, but that so far there is limited evidence to establish a concrete link with the evolution to SARS-CoV-2.